Static Analysis of the Honeycomb Sandwich Plate With GNPs Facesheets Using an Isogeometric Approach - Hoang, Minh Anh; Nguyen , Tri Dung; Pham, Tan Hung (Journal of Technical Education Science, 2025)
This paper investigates the static behavior of auxetic honeycomb sandwich plates with graphene nanoplatelet (GPN)-reinforced aluminum face sheets based on a refined plate theory (RPT) and isogeometric analysis (IGA). The RPT incorporates the effects of transverse shear deformation without requiring shear correction factors, while the auxetic honeycomb core enhances the mechanical performance of the sandwich structure. The effective properties of the GPNs-reinforced composite face sheets are determined using a modified Halpin-Tsai micromechanical model under uniform nanoparticle distribution. Integrating RPT with IGA enables exact geometry representation and high-order continuity, offering advantages over conventional finite element method despite the higher computational cost for large basis functions. Numerical studies are carried out to evaluate the influence of parameters, such as nanoparticle weight fraction, honeycomb geometry, and boundary conditions on the static response of the sandwich plate. The results confirm the effectiveness and reliability of the proposed approach, highlighting that the combination of auxetic cores and GPNs reinforcement substantially improves structural stiffness and static behavior, providing useful guidance for the design of advanced lightweight structures.